Content analysis of clinical questions from Australian general practice which are prioritised for answering: identifying common question types and perceived knowledge gaps. Issue 1 (24th June 2019) - Muscat, Danielle Marie; Patel, Pinika; Reid, Sharon; Hoffmann, Tammy; Albarqouni, Loai; Trevena, Lyndal
Abstract : Perceived knowledge gaps in general practice are not well documented but must be understood to ensure relevant and timely evidence for busy general practitioners (GPs) which reflects their diverse and changing needs. The aim of this study was to classify the types of questions submitted by Australian GPs to an evidence-based practice information service using established and inductive coding systems. We analysed 126 clinical questions submitted by 53 Australian GPs over a 1.5-year period. Questions were coded using the International Classification of Primary Care (ICPC-2 PLUS) and Ely and colleagues' generic questions taxonomy by two independent coders. Inductive qualitative content analysis was also used to identify perceived knowledge gaps. Treatment (71%), diagnosis (15%) and epidemiology (9%) were the most common categories of questions. Using the ICPC-2 classification, questions were most commonly coded to the endocrine/metabolic and nutritional chapter heading, followed by general and unspecified, digestive and musculoskeletal. Seventy per cent of all questions related to the need to stay up-to-date with the evidence, or be informed about new tests or treatments (including complementary and alternative therapies). These findings suggest that current guideline formats for common clinical problems may not meet the knowledge demands of GPs and there is gap in access to evidence updates on new tests, treatments and complementary and alternative therapies. Better systems for 'pulling' real-time questions from GPs could better inform the 'push' of more relevant and timely evidence for use in the clinical encounter.